Penyuluhan Infeksi Kecacingan Pada Anak-Anak Pemulung di Tempat Pembuangan Akhir Alak Kota Kupang - Ni Made Susilawati; Meliance Bria (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2023)
Worm infection is a health problem that often occurs throughout the world, especially in Indonesia with a high prevalence. One of the most common helminthic infections in Indonesia is the Soil Transmitted Helminths worm. Children are an age group that is susceptible to this infection. Worm infections can have serious consequences if not treated with deworming medication and a clean and healthy lifestyle for the person. This community service is carried out with the aim of conducting counseling about environmental health, especially in helminthiasis at the Alak Final Disposal Site, Kupang City. This activity conducts counseling and examination of the community on how to deal with helminthiasis in children. Subjects as many as 30 children. The worm examination was carried out using the direct slide method and then observed under a microscope with a magnification of 10x-40x. Based on the results of the examination found Ascaris lumbricoides eggs by 10%. So based on the results of this service it shows that there is a prevalence of worm infection in the Alak Final Disposal Site. Therefore, it is suggested to parents and especially children to further improve the Clean and Healthy Lifestyle (PHBS) to avoid worm infection.